2019
DOI: 10.1590/0102-311x00108018
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the protocol of a pilot randomized controlled trial for the recovery-oriented intervention to people with psychoses in two Latin American cities

Abstract: Several Latin American countries have made remarkable strides towards offering community mental health care for people with psychoses. Nonetheless, mental health clinics generally have a very limited outreach in the community, tending to have weaker links to primary health care; rarely engaging patients in providing care; and usually not providing recovery-oriented services. This paper describes a pilot randomized controlled trial (RCT) of Critical Time Intervention-Task Shifting (CTI-TS) aimed at addressing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…One exception is a study we conducted in Santiago, Chile, which incorporated peer workers into a community mental health intervention, called Critical Time Intervention—Task Shifting (CTI-TS), to support users with schizophrenia ( 65 ). A qualitative study that evaluated the users' experience with CTI-TS found that the users felt a special connection and reciprocity with the peer workers, who had also experienced psychosis ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…One exception is a study we conducted in Santiago, Chile, which incorporated peer workers into a community mental health intervention, called Critical Time Intervention—Task Shifting (CTI-TS), to support users with schizophrenia ( 65 ). A qualitative study that evaluated the users' experience with CTI-TS found that the users felt a special connection and reciprocity with the peer workers, who had also experienced psychosis ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Centro de Atenção Psicossocial -CAPS), while in Santiago it was conducted within users' homes and surrounding neighborhoods. These adaptations were drafted collaboratively by researchers at Columbia University, Universidade Federal do Rio de Janeiro, and Universidad de Chile, and informed by their experience developing and piloting CTI in Brazil (Mascayano et al ., 2019 ).…”
Section: Adapting Cti For the La Settingmentioning
confidence: 99%
“…the task-shifting/task-sharing strategy and the community-based aspect – remained the same due to the dearth of mental health professionals as well as the cultural profile of both the settings. Other elements of the intervention were also similar across sites; for example, the structure and contents of the worker-pair trainings were standardized and manualized (Mascayano et al ., 2019 ).…”
Section: Adapting To the Community Conditions Through Modifying The Intervention Settingmentioning
confidence: 99%
“…For example, although over 80% of people treated for FEP in Chile receive medications, only 40% receive other important services such as support for education and employment, family counseling, and peer support [ 8 , 9 ]. Moreover, when these other services are offered, they tend to be ad-hoc because most mental health providers are not appropriately trained in evidence-based approaches (i.e., psychosocial interventions) for psychosis [ 9 , 10 ]. This is the gap that is being addressed by the current study by first adapting OnTrackChile (OTCH) from OnTrackNY (OTNY), a coordinated specialty care (CSC) program for FEP currently being implemented across the US, and then examining its effectiveness and implementation across five different regions in Chile.…”
Section: Introductionmentioning
confidence: 99%